Entrances to strategic refocus to improve the performance and balance of the corporate activities portfolio: the case of the National Painting Establishment in Algeria - ENAP - Meddah Araibi Elhadj; Ishak Kherchi (Dirassat Journal Economic Issue, 2017)
This study aims to analyze the core business on the firm’s business portfolio and research the different modes of strategic refocusing on core business to improve performance and balance portfolio. The practice study interest to analyze the strategic position by using BCG model on the Algerian National Paintings Company. The study’s conclusion resolves this problematic of performance and balance of portfolio activity by redefine core business and formulate different adequate strategic business unit to the new future company strategic position.